(untitled) (Eurasian Journal of Philology Science and Education, 2025)
The article discusses the methodological foundations of the introduction of massive open online courses (MOOCs) into the higher education system and their role in the process of training future teachers of Russian language and literature. The review of the impact of MOOCs on the educational process is carried out, the main formats of their application in educational programs are analyzed: blended learning, the transition to an online format, the expansion of the interaction space between students and teachers, as well as the use of electronic resources. The study describes the main stages of MOOC creation, among which an important place is occupied by studying the target audience, structuring the material, correlating theoretical knowledge with practical tasks and taking into account linguistic and didactic features. In addition, the possibilities of developing professional competencies and building an individual educational trajectory of students using digital technologies are discussed. The article discusses the possibilities and prospects of massive open online courses (MOOCs) in the higher education system, and reveals their role in improving teaching methods. The authors give examples of MOOC platforms (Coursera, EdX, FutureLearn) and consider the results of their application in international practice. The theoretical basis of the research is scientific concepts related to digital pedagogy, teaching methods and ICT competence. The article is relevant from the point of view of individualizing learning and developing intercultural competence, analyzing the advantages and difficulties of implementing and applying MOOCs. Keywords: digital technologies, information and educational environment, communication competence, massive open online courses (MOOCs), professional activity.